Certificate For Occupancies (CFO) and Certificate of Completion and Compliances (CCC): are customers satisfied? / Norisfarizan Ismail...[et al.] - Ismail, Norisfarizan; Ramli, Azura; Zahari, Mohd. Izwan; Ahmad, Jasmine (2010)
This study focuses on identifying the factors causing delay on issuing Certificate of Completion and Compliance (CCC) and customer’s level of awareness on the process of getting those certificates. Certificate of Completion and Compliances (CCC) is an official certificate which acknowledged and certify that the building was complete and safe for occupation with complete infrastructure and comply with regulations under the Local Government Act 1976 (Act 171) and Uniform Building By-Law (UBBL). Previously, the issuance of CCC (formerly known as CF) would take about three to sixth month or even a year. In 2007 the Malaysian government reviewed the process and gave resposibility to professional architects and engineers instead of local authorities to issue the CCC. This is to reduce red-tape and to ensure that house buyers and building owners get to move in as quickly as possible without compromising their safety. Buyers are promised a time period of two weeks for CCC. Unfortunately until today, there are complaints from buyers about developers’ failure in issuing CCC on time. Questionnaires were distributed to obtain perception from relevant parties especially developers and buyers.The outcome of the study could contribute to the improvement of services to the relevant bodies.